A New, Portable Orofacial Manometer for Measuring Tongue Strength and Endurance in Children: Laboratory-Based Validity Study - Rizky Kusuma Wardhani; Luh Karunia Wahyuni; Widjajalaksmi Kusumaningsih; Sarworini Bagio Budiardjo; Prasandhya Astagiri Yusuf; Sri Mardjiati Mei Wulan; Aria Kekalih; Titis Prawitasari; Sawitri Darmiati; Boya Nugraha (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundAn accurate tongue strength and endurance assessment is necessary for pediatric dysphagia. TongueFit is a new, portable orofacial manometer for measuring tongue strength and endurance and a game-based training app for children. ObjectiveThis study aimed to test the validity of TongueFit compared with a standard manometer as the current gold standard for measuring air pressure. MethodsThis laboratory study compared TongueFit and a standard manometer as the gold standard for measuring air pressure. This study was conducted in 3 different experimental conditions. The first experiment compared TongueFit and the standard manometer using a force tester (MCT-2150), with pressure controlled by MSatLite software. The second and third experiments involved 2-cm and 3-cm bulbs between the 2 devices. This study used Lin concordance correlation to measure the level of agreement. ResultsThere was a mean absolute difference of 0.005 kilopascals (kPa) between the TongueFit and the standard manometer (n=35, ρC=1). Statistical analysis showed perfect agreement correlation (ρC=1). By using the 2-cm bulb, TongueFit’s mean was 0.007 kPa lower, also showing perfect agreement (ρC=1). Furthermore, using the 3-cm bulb, results showed almost perfect agreement (ρC=0.999) with the TongueFit’s mean, which was 0.044 kPa lower. ConclusionsThis study confirms the high validity of TongueFit as an orofacial manometer compared with a standard manometer, with negligible mean differences, as well as near-perfect and perfect agreement in the experiments. These results confirm that TongueFit is a valid and accurate tool for assessing tongue strength.